2016
DOI: 10.1111/1744-7941.12106
|View full text |Cite
|
Sign up to set email alerts
|

IHRMand expatriation inJapaneseMNCs:HRMpractices and their impact on adjustment and job performance

Abstract: Studies of international human resource management (IHRM) have pointed out that Japanese multinational companies (MNCs) tend to use more parent‐country nationals (PCNs) than do western MNCs. The ethnocentric staffing policies imply that the management of expatriation has a greater influence on the success of Japanese MNCs. We use survey data from 149 Japanese repatriates to examine the relationship between IHRM practices – selection, preparation and corporate support – and expatriate adjustment and job perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
45
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 90 publications
(159 reference statements)
1
45
0
1
Order By: Relevance
“…Holopainen and Bjo¨rkman (2005) stressed the importance of communication ability for expatriate success. Furusawa and Brewster (2016) found that language ability was positively related to work adjustment. Researchers generally agreed on the importance of such communication ability but some disagreement exists among researchers on linguistic ability.…”
Section: Relationship Between Social Competencies and Job Performancementioning
confidence: 98%
See 4 more Smart Citations
“…Holopainen and Bjo¨rkman (2005) stressed the importance of communication ability for expatriate success. Furusawa and Brewster (2016) found that language ability was positively related to work adjustment. Researchers generally agreed on the importance of such communication ability but some disagreement exists among researchers on linguistic ability.…”
Section: Relationship Between Social Competencies and Job Performancementioning
confidence: 98%
“…Furusawa and Brewster (2016) found that relational abilities were associated with job performance. Solomon et al, (2009) further stressed that the relationship dimension is the foundation of all interpersonal interactions.…”
Section: Relationship Between Social Competencies and Job Performancementioning
confidence: 99%
See 3 more Smart Citations